Educação e cidadania: perspectivas da literacia digital crítica - Michele Mezari Oliveira; Graziela Fatima Giacomazzo (EccoS – Revista Científica)
This paper presents a research that investigated the concept of digital literacy in studies published in the Scielo Brazil, Portugal and Spain databases . From the concept as it is presented in the various studies the conceptualization of a critical digital literacy is pursued. This perspective refers directly to human formation in the contemporary world and to the relationship between education and digital citizenship. It considerates the understanding of the concept of technology in its ideological dimension, putting centrality in the condition of the subjects in the digital media. Three categories of analysis are explained by the study - Ideological Representation, Ideological Positioning and Ideological Production that seek to provide analytical subsidies for the state of appropriation of the subject in the perspective of critical digital literacy. The theoretical contribution is anchored in critical social philosophers such as Heidegger (2007), Marcuse (1973), Feenberg (2010, 2012) and especially Vieira Pinto (2005), Brazilian philosopher, among other authors who contributed to the debate and Concepts of technology and digital literacy.